Diagnostic accuracy of calf circumference for decreased muscle mass in older adults with sarcopenia - Novi Diah Pusparini; Enny Probosari; Etisa Adi Murbawani; Siti Fatimah Muis; Febe Christianto (Journal of Biomedicine and Translational Research, 2022)
Background: Increasing number of the older adults population results in increasing sarcopenia, a geriatric problem that may lead to poor quality of life, susceptibility to disease, malnutrition, and even death. Muscle mass is an important sarcopenia parameter that can be measured by Bioelectrical Impedance Analysis (BIA). Detection of decreased muscle mass can be done by measuring calf circumference, it is expected to provide an early diagnose of sarcopenia so that early intervention can be given and improve the quality of life of the older adults.Objective: To analyze the diagnostic accuracy of calf circumference for decreased muscle mass in older adults to provide simple way in diagnosing sarcopenia.Methods: This study involved 126 older adults, consisted of 57 men and 69 women aged 60-80 years in the community who met the inclusion criteria. Criteria of sarcopenia were defined based on the Asian Working Group for Sarcopenia (AWGS) Consensus, consisted of three components; muscle mass, handgrip strength, and walking speed. This study analyze the diagnostic accuracy of calf circumference for decreased muscle mass measured by single- frequency BIA and calf circumference was measured using a measuring tape. The analysis was carried out according to the receiver operating characteristic (ROC) curve to determine the cut-off point along with the sensitivity (Se) and specificity (Sp) values, positive and negative predictive values (PPV and NPV) of calf circumference as an indicator for low muscle mass.Results: Optimal cut-off point of calf circumference to indicate low muscle mass is 32.9 cm in women (Se 80.8%, Sp 79.1%, PPV 75.9%, NPV 87.5%) and 33.5 cm in men (Se 78.6%, Sp 74.4%, PPV 50%, NPV 91.4%). PPV in men is lower than women. This is due to a lower prevalence of decreased muscle mass in men than women. There were 49 participants with the calf circumference below cut-off point and 40 (31.7%) of the 126 participants had sarcopenia.Conclusion: Calf circumference has a diagnostic accuracy to find decreased muscle mass in  sarcopenia.